A 2-D Kinetic Theory for Flows of Monodomain Polymer-Rod Nanocomposites (Communications in Computational Physics, 2018)
We merge classical kinetic theories [M. Doi and S. F. Edwards, The Theoryof Polymer Dynamics, 1986] for viscous dispersions of rigid rods, extended to semi-flexibility [A. R. Khokhlov and A. N. Semenov, Macromolecules, 17 (1984), pp. 2678-2685], and for Rouse flexible chains to model the hydrodynamics of polymer nano-rodcomposites (PNCs). A mean-field potential for the polymer-rod interface provides thekey coupling between the two phases. We restrict this first study to two-dimensionalconformational space. We solve the coupled set of Smoluchowski equations for threebenchmark experiments. First we explore how rod semi-flexibility and the polymerrodinterface alter the Onsager equilibrium phase diagram. Then we determine monodomainphase behavior of PNCs for imposed simple elongation and shear, respectively.These results inform the effects that each phase has on the other as parametricstrengths of the interactions are varied in the context of the most basic rheological experiments.